Text and Context of the Blaan’s Folk Literature - Benito, Neva (JPAIR Multidisciplinary Research, 2020)
Blaans are one of the tribes that reside in the Mindanao archipelago in the Philippines. This study collected, transcribed, classified, and analyzed Blaan folk literature in the barangays of Sinapulan and Eday in the municipality of Columbio, Sultan Kudarat. This also sought to identify the context that brought about the folk literature’s citation and identified the beliefs and practices embedded in these literary texts. This Blaan oral literature was transcribed and translated in Cebuano or Filipino by the informants and analyzed using Alan Dundes’ theory of analyzing folklore- through its text, and context. The gathered Blaan folk literature was classified as occasional songs, work songs, and prose narratives depicting legends, and creation stories. It was also found out that the folk literature was recited during important occasions like weddings, tribal assemblies either as a form of entertainment or a form of reminder for the members in the importance of tribal peace and unity as well as their role in protecting nature and their environment. This study also revealed that Blaan folk literature embodies the tribe’s values and ideals like generosity, courage, bravery, and traditions like the giving of dowry to their intended bride. They also valued nature and believed in the Supreme Being, whom they call Dwata but whose traits are like the Christian god.